MUSEQuBES: Connecting H i Absorption with Lyα Emitters at z ≈ 3.3 - Eshita Banerjee; Sowgat Muzahid; Joop Schaye; Jérémy Blaizot; Nicolas Bouché; Sebastiano Cantalupo; Sean D. Johnson; Jorryt Matthee; Anne Verhamme (The Astrophysical Journal)
We present a comprehensive analysis of H i absorption around 96 Ly α emitters (LAEs) at z ≈ 3.3 (median Ly α luminosity ≈10 ^42 erg s ^−1 ). These LAEs were identified within eight MUSE fields, each $1^{′} × 1^{′} $ on the sky and centered on a bright background quasar, as part of the MUSEQuBES survey. Using Voigt profile fitting for all H i absorbers detected within ±​​​​​​500 km s ^−1 of these LAEs, we compiled a catalog of 800 H i absorption components. Our analysis shows that H i absorption is enhanced near the LAEs compared to the intergalactic medium. However, no trend is found between the column densities of H i absorbers and their impact parameters from the LAEs (spanning ​​​​​​≈54–260 pkpc). Additionally, all galaxies associated with Lyman-limit systems have impact parameters >50 pkpc from the quasar sightlines, suggesting that true absorber hosts may be too faint to detect. The LAEs show an overall H i covering fraction ( f _c (H i )) of ≈88% for a threshold ${{\rm{log}}}_{10}(N/{{\rm{cm}}}^{-2})$ (H i ) = 15. Notably, at the same threshold, the LAEs in pairs/groups exhibit a 100% H i covering fraction out to ≈250 pkpc. In contrast, isolated LAEs consistently show a lower f _c (H i ) of ≈80%. This environmental influence on f _c (H i ) is also evident up to ≈300 km s ^−1 in differential bins of line-of-sight velocity. We find an anticorrelation between f _c (H i ) and the equivalent width of rest-frame Ly α emission (EW _0 ). Based on the Ly α shell model, this could imply that gas-rich galaxies tend to reside in gas-rich environments or that the LAEs with higher EW _0 are more efficient at ionizing their surrounding medium.